Hubungan pengetahuan, sikap dan tindakan hygiene sanitasi pedagang makanan jajanan di pinggir jalan - Rahmayani Rahmayani (AcTion: Aceh Nutrition Journal, 2018)
Traders do not wash hands at the time and before touched food and there are peddle food in the open side of the road and touch the food without using tools. This indicates that the risk of food sold can be contaminated with germs that cause foodborne illness. The aim of research to measure the correlation between knowledge, attitude and practice with the hygiene and sanitation of street food. This research is quantitative research with a cross-sectional design. The population of this research is all traders in the roadside in Elementary School 20 and 24 Banda Aceh which amount to 54 people and also become a sample of research. From the result of research known there is no relation between knowledge with hygiene sanitation of street food trader in elementary school with p-value 0,146. there is a correlation between attitude with hygiene sanitation of street food merchants in elementary school with 0,041. there is a correlation between the action with hygiene sanitation of street food vendors in elementary school with p-value 0,042. It is expected that the socialization of the Health Office on the importance of food sanitation hygiene to the traders.Pedagang tidak mencuci tangan saat dan sebelum menjamah makanan ada yang menjajakan makanan dalam keadaan terbuka dipinggir jalan serta menjamah makanan tanpa menggunakan alat. Hal ini mengindikasikan bahwa adanya risiko makanan yang dijajakan dapat tercemar kuman penyakit yang mengakibatkan penyakit bawaan makanan. Tujuan penelitian untuk mengukur hubungan pengetahuan, sikap dan tindakan dengan hygiene dan sanitasi makanan jajanan. Penelitian ini merupakan penelitian kuantitatif dengan rancangan cross sectional. Populasi penelitian ini adalah seluruh pedagang yang ada di pinggir jalan di Sekolah Dasar 20 dan 24 Banda Aceh yang berjumlah 54 orang dan sekaligus menjadi sampel penelitian. Hasil penelitian diketahui tidak ada hubungan antara pengetahuan dengan hygiene sanitasi pedagang makanan jajanan di pinggir jalan di Sekolah Dasar dengan p value 0,146. ada hubungan antara sikap dengan hygiene sanitasi pedagang makanan jajanan di pinggir jalan di Sekolah Dasar dengan 0,041. ada hubungan antara tindakan dengan hygiene sanitasi pedagang makanan jajanan di pinggir jalan di Sekolah Dasar dengan p value 0,042. Diharapkan adanya sosialisasi dari Dinas Kesehatan tentang pentingnya higiene sanitasi makanan kepada para pedagang.